THE RELIEF PROVIDED TO A COMPLAINANT UNDER SECTION 163(1)(a) OF THE 2008 COMPANIES ACT: AN EXAMINATION OF THE CRITERION WITH REFERENCE TO PEEL v HAMON J&C ENGINEERING (PTY) LTD - Simphiwe S Bidie (Obiter, 2021)
The remedies in favour of minority shareholders that have developed over the years have been informed by the discriminatory manner in which the proper-plaintiff rule has been applied within the management of companies, in disregard of the rights and interests of minority shareholders. Broadly, section 163(1) of the Companies Act 71 of 2008 accords shareholders or directors of a company three circumstances in which they have rights to apply to court for relief. One ground for application is that an act or omission of a company, or a related person, has had a result that is oppressive or unfairly prejudicial to, or that unfairly disregards the interests of, the applicant. From the contemporary debates and court decisions consulted, it is clear that the criterion that complainants must satisfy under section 163(1) – “any act or omission of the company, or a related person, has had a result”, – and the manner in which parties must go about meeting such criterion, is not yet settled. The intention of this paper is to analyse and examine this criterion. The paper seeks to contribute to the debate by using the case of Peel v Hamon J&C Engineering (Pty) Ltd as the point of reference. The case is pertinent because it touches on all the elements that must be satisfied under section 163(1). Secondly, much as the decision is supported, it seems an error of law was made in one aspect of the decision.